(untitled) (Educological discourse, 2016)
The article describes the results of a study of reference relations of students with signs of musical talent. Reference relations as a source of socialization are the resource for spiritual development, because they have a direct impact on consciousness and self-awareness formation and selection of areas for self-realization. It has been established that the greatest influence on students’ musical abilities development have parents and music teachers. Next are friends and reference classmates who study with a specialization in «Musical art». Next in importance group make well known creative personalities, mostly musicians. The feature of this group is its virtuality, since the vast majority of people who make it, are not part of the contact environment. Referentiality of school teachers and classmates appeared to be insignificant. The analysis revealed two types of referentiality 1) referentiality aimed at personal values and motivational support, which is provided by parents and relatives; 2) referentiality, based on the professional assessment of skills and development abilities, which is obtained from the relations with music teachers. These two types of referentialities are united by emotional and value attitude to music, which creates a sense of community and unity with others in the experience of beauty and harmony, and is an important component of spiritual development.